2016
DOI: 10.1038/ncomms12172
|View full text |Cite
|
Sign up to set email alerts
|

Direct detection of a single photon by humans

Abstract: Despite investigations for over 70 years, the absolute limits of human vision have remained unclear. Rod cells respond to individual photons, yet whether a single-photon incident on the eye can be perceived by a human subject has remained a fundamental open question. Here we report that humans can detect a single-photon incident on the cornea with a probability significantly above chance. This was achieved by implementing a combination of a psychophysics procedure with a quantum light source that can generate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
128
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(139 citation statements)
references
References 30 publications
7
128
0
4
Order By: Relevance
“…[22] It has recently been shown that human eyes can sense single photons. [23] Videos of single particle interference show that the apparent wave nature only emerges when large numbers of photons create a quasicontinuous pattern characteristic of a classical wave. [24] [13] Our program replaces the classical interpretation of diffraction and interference with the idea that whenever light is allowed to take two alternative paths, then the phenomenon of interference occurs.…”
Section: Gravitational Wave Detectors and The Quantum Properties Of Lmentioning
confidence: 99%
“…[22] It has recently been shown that human eyes can sense single photons. [23] Videos of single particle interference show that the apparent wave nature only emerges when large numbers of photons create a quasicontinuous pattern characteristic of a classical wave. [24] [13] Our program replaces the classical interpretation of diffraction and interference with the idea that whenever light is allowed to take two alternative paths, then the phenomenon of interference occurs.…”
Section: Gravitational Wave Detectors and The Quantum Properties Of Lmentioning
confidence: 99%
“…The human eye has a unique ability to adapt to a wide range of brightness levels ranging from a bright sunny day down to single photon levels [25,26]. Conventional sensors cannot simultaneously reliably capture very dark and very bright regions in many natural scenes.…”
Section: Extreme Dynamic Range Of Pf-spadsmentioning
confidence: 99%
“…For instance, photoreceptors in humans can detect single photons (Tinsley et al 2016), and hair cells can detect mere nanometers of displacement of their stereocilia (Martin & Hudspeth 1999). The research challenge for these fields is how the signal is distinguished among the noise in these ultrasensitive detectors.…”
Section: Criteria For a Magnetosensory Neuron And Receptormentioning
confidence: 99%